The extract of Nicotiana glauca induces apoptosis in rhabdomyosarcoma cells - Pronsato, Lucía (2025)
Rhabdomyosarcoma, a malignant tumor commonly found in children and adolescents, often carriesa poor prognosis. We conducted studies on the effects of the liposoluble extract of Nicotiana glauca (N. glauca), a plant from the Solanaceae family that is widely distributed, on the C2C12 murine myoblast cell line. We additionally investigated the antiproliferative effects of the extract on the RD rhabdomyosarcoma tumor cell line. The RD cells were pre-incubated without fetal bovine serum, followed by treatment with the liposoluble extract and the n-hexane sub-extract at specific concentrations. The effects on cell morphology were assessed using staining techniques. Cell viability, growth, and division capacities were evaluated through a wound assay. We analyzed the expression levels and subcellular localization of several proteins, including β-catenin, Notch 1, Caspase 3, and 14-3-3, using Western blotting. The extract of N. glauca induces apoptosis in C2C12 cells, suggesting that it may possess antitumor properties and could potentially be used in the treatment of hyperproliferative disorders. Our findings revealed that the control cells exhibited intact and normal nuclei, while the treated cells displayed characteristic morphological changes associated with apoptosis. Also, the treatments significantly reduced cell division capacity, andpotentially cell migration, compared to the control group. Moreover, the evaluation of β-catenin protein localization showed a cytoplasmic and membrane proximity in C2C12 cells, whereas RD cells exhibited nuclear localization. These findings suggest the potential therapeutic value of the extract in targeting the proliferation and spread of rhabdomyosarcoma cells.